PSYCHOLOGİCAL İSSUES OF DEVELOPİNG EMOTİONAL ATTİTUDES AND EMOTİONAL: İNTELLİGENCE İN STUDENTS - Babayeva, Firangiz (Health and Society, 2025)
The article analyzes the ways and means of developing emotional intelligence in students. The study investigated the possibilities of reducing various stress factors during the implementation of programs related to emotional intelligence. The study showed that there is a positive relationship between the levels of negative emotions and the level of emotional intelligence. This relationship is significant at the p=0.05 level with a low level of negative emotions. It was found that the higher the ability to manage emotions and manage the intrapersonal state, the less negative emotions are observed in the behavior and actions of students.